A Cl− Hinge for Cyclen Macrocycles: Ionic Interactions and Tweezer–Like Complexes - Avilés–Moreno, Juan Ramón; Berden, Giel; Oomens, Jos; Martínez–Haya, Bruno (Frontiers in Chemistry, 2019)
The supramolecular networks derived from the complexation of polyazamacrocycles with halide anions constitute fundamental building blocks of a broad range of modern materials. This study provides insights into the conformational framework that supports the binding of protonated cyclen macrocyles (1,4,7,10-Tetraazacyclododecane) by chloride anions through NH+...Cl- interactions. The isolated complex comprised of two cyclen hosts linked by one Cl- anion is characterized by means of infrared action spectroscopy and ion mobility mass spectrometry, in combination with quantum chemical computations. The Cl- anion is found to act as a hinge that bridges the protonated NH2+ moieties of the two macrocycles leading to a molecular tweezer configuration. Different types of conformations emerge, depending on whether the trimer adopts an open arrangement, with significant freedom for internal rotation of the cyclen moieties, or it locks in a folded conformation with intermolecular H-bonds between the two cyclen backbones. The ion mobility collision cross section supports that folded configurations of the complex are dominant under isolated conditions in the gas phase. The IRMPD spectroscopy experiments suggest that two qualitatively different families of folded conformations coexist at room temperature, featuring either peripheral or inner positions of the anion with respect to the macrocycle cavities, These findings should have implications in the growth of extended networks in the nanoscale and sensing.